Evaluation of hepatoprotective potential of aqueous extract of Withania somnifera in albino rats - Sharma, Monica; Gaur, Anand; Vishwakarma, Pinki; Goel, Raj Kumar; Saxena, K. K. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: Hepatic diseases are a major cause of morbidity and disability of work force throughout the world. The treatment of hepatic diseases with standard drugs poses the risk of toxicity on various organ systems. Withania somnifera, a herbal plant has been claimed to be effective in the treatment of various types of hepatic conditions. The present study was undertaken to explore the hepatoprotective activity of aqueous extract of Withania somnifera (AEWS) in experimentally induced hepatotoxicity in albino rats. Methods: The study was commenced after obtaining approval from institutional animal ethical committee using AEWS leaves in Albino wistar rats (150-200 gm) of either sex. The hepatoprotective activity was evaluated using biochemical examination. The animals were divided into five groups of six animals each. In each experiment, first group was given normal saline (1 ml/kg/day), second group was injected with toxin CCl4 (1 ml/kg) i.p only once to produce hepatotoxicity, third and fourth groups were given Withania somnifera orally (500 mg/kg and 1000 mg/kg) (respectively), as a single dose per orally every morning and fifthgroup was given standard drug Liv-52 (1 mg/kg). Results: Aqueous extract of Withania somnifera leaves in oral dose exhibited significant hepatoprotective effect in all models used in this study. Conclusions: It can be concluded from our study that aqueous extract of Withania somnifera leaves possesses hepatoprotective activity.